2005
DOI: 10.3348/jkrs.2005.53.5.343
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Mass-forming Type Peripheral Cholangiocarcinoma and Hepatic Abscesses: Application of Artificial Neural Networks to CT Images

Abstract: Several CT features of hepatic abscesses have been reported (1 4). Some hepatic abscesses occasionally mimic other hepatic tumors on CT, and some malignant hepatic tumors such as metastases, cholangiocarcinoma (CC), and leiomyosarcoma, may also mimic hepatic abscesses (5 12). Since the treatment strategy differs based on the possibility of malignancy, differentiation of hypovascular liver tumors such as CC or metastasis from hepatic abscesses on CT is important. A variety of radiologic procedures have been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, this is the first case in the English medical literature of a hepatic parasitic abscess caused by clonorchiasis without any perceptible dilatation of the intrahepatic bile ducts, as seen on CT scans. Seong et al ( 7 ) reported that the following CT findings favor hepatic abscess over the mass-forming type intrahepatic cholangiocarcinoma: multilayered enhancement, a sharp margin, inner air-density, a cluster sign, an air-biliary gram, a lobulated configuration, atelectasis of the lower lungs, pleural effusion and transient hepatic attenuation difference. In daily practice, however, such differentiation poses difficulty given the considerable overlap of the CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case in the English medical literature of a hepatic parasitic abscess caused by clonorchiasis without any perceptible dilatation of the intrahepatic bile ducts, as seen on CT scans. Seong et al ( 7 ) reported that the following CT findings favor hepatic abscess over the mass-forming type intrahepatic cholangiocarcinoma: multilayered enhancement, a sharp margin, inner air-density, a cluster sign, an air-biliary gram, a lobulated configuration, atelectasis of the lower lungs, pleural effusion and transient hepatic attenuation difference. In daily practice, however, such differentiation poses difficulty given the considerable overlap of the CT findings.…”
Section: Discussionmentioning
confidence: 99%